RENEWAL OF THE NATIONAL CONTRACT LAW - Latifiani, Dian (Jurnal Hukum Progresif, 2020)
The development of transactions/contracts in Indonesia and the world is developing very rapidly. Meanwhile, Indonesian contract law is sourced from the Civil Code Book III. The Dutch colonial-made Burgerlijk Wetboek did not yet regulate national and international contracts which had undergone development. Indonesian values also do not exist in book III. So it is necessary to have contract law renewal based on the values of Pancasila. The problem discussed in this paper is how to reform the national contract law. The urgency for renewal is carried out to support the 2005-2025 National RPJP, namely "The development of legal materials/substances is directed to continue the renewal of legal products to replace colonial legacy laws to reflect the social values and interests of the Indonesian people". The juridical normative writing method is used to assess the value of the renewal of the national contract law. Renewal begins with the preparation of an academic paper. Updates are carried out with open partial codification, not closed. The reforms contain Pancasila values, are designed as a sub-codification of engagement law, and are designed to lay the foundation for contract law in Indonesia.